The effect of yellow pumpkin on improving nutritional status in toddlers: A literature review - Ratnawati, Ratnawati; Sunarti, Sunarti; Mulasari, Surahma Asti (Institute of Computer Science (IOCS), 2024)
One of the most important markers of child health and growth is nutritional condition. Malnutrition raises the risk of illness and can disrupt mental and physical development. Due to its high vitamin content, pumpkin is one way to enhance children' nutritional status. Nutritional intervention is crucial. Through a review of the literature, this study seeks to determine how well pumpkin can improve toddlers' nutritional status. This study assessed the impact of pumpkin on toddlers' nutritional status using a literature review and the PRISMA methodology. Google Scholar and ProQuest were searched, yielding 1,699 and 3 articles, respectively. Eight pertinent articles were chosen after selection based on inclusion and exclusion criteria. The findings demonstrated that processed pumpkin products, such pudding and biscuits, improved the weight and nutritional condition of malnourished children. After consuming pumpkin seed pudding, there was a noticeable increase in weight, and pumpkin cookies also had a role. Pumpkin helps malnourished children gain weight and improve their nutritional condition.